2002
DOI: 10.1017/s0004972700020621
|View full text |Cite
|
Sign up to set email alerts
|

Construction of sunny nonexpansive retractions in Banach spaces

Abstract: Let J be a commutative family of nonexpansive self-mappings of a closed convex subset C of a uniformly smooth Banach space X such that the set of common fixed points is nonempty. It is shown that if a certain regularity condition is satisfied, then the sunny nonexpansive retraction from C to F can be constructed in an iterative way.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 7 publications
0
19
0
Order By: Relevance
“…Closely related to this field is the problem of finding a common fixed point of a given family of operators. In this direction, several iterative methods have been developed for these problems, see [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. In recent years, viscosity approximation methods have been developed for finding the approximate solutions of the family of operators.…”
Section: Introductionmentioning
confidence: 99%
“…Closely related to this field is the problem of finding a common fixed point of a given family of operators. In this direction, several iterative methods have been developed for these problems, see [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. In recent years, viscosity approximation methods have been developed for finding the approximate solutions of the family of operators.…”
Section: Introductionmentioning
confidence: 99%
“…We know that Fi x(S) is nonempty if C is bounded (see [44]). Now, we present the concept of a uniformly asymptotically regular semigroup (see [34][35][36]). …”
Section: Remark 42mentioning
confidence: 99%
“…Suzuki [7] was the first to introduce again in a Hilbert space the following implicit iteration process: 4) for the nonexpansive semigroup case. In 2002, Benavides et al [8] in a uniformly smooth Banach space, showed that if S satisfies an asymptotic regularity condition and {a n } fulfills the control conditions lim n→∞ α n = 0, ∞ n=1 α n = ∞, and lim n→∞ α n α n +1 = 0 , then both the implicit iteration process (1.4) and the explicit iteration process (1.5) 5) converge to a same point of F(S). In 2005, Xu [9] studied the strong convergence of the implicit iteration process (1.1) and (1.4) in a uniformly convex Banach space which admits a weakly sequentially continuous duality mapping.…”
Section: Lemma 13mentioning
confidence: 99%
“…The strong convergence theorem of {x n } is proved in a reflexive Banach space which admits a weakly sequentially continuous duality mapping. Very recently, motivated by the above results, Chen et al [11] proposed the following two modified Mann iterations for nonexpansive semigroups {T(t) : 0 ≤ t < ∞} and obtained the strong convergence theorems in a reflexive Banach space E which admits a weakly sequentially continuous duality mapping: 8) and 9) where f : C C is a contraction. They proved that the implicit iterative scheme {x n } defined by (1.8) converges to an element q of Fix(S), which solves the following variation inequality problem:…”
Section: Lemma 13mentioning
confidence: 99%